Correlation between obesity and severity of distal radius fractures - Acosta Olivo, Carlos Alberto; González Saldivar, J. C.; Villarreal Villarreal, Gregorio Alejandro; Torres Botello, A.; Gómez García, E.; Tamez Mata, Yadira Alejandra; Peña Martínez, Víctor Manuel (2017)
Introduction: The incidence of obesity has increased significantly worldwide. Our hypothesis was that patients with obesity have a more severe distal radius fracture and we realized a study to evaluate this correlation between obesity and severity of distal radius fractures caused by low-energy injuries. Materials and methods: A total of 114 patients with distal radius fracture were examined in a